Career adaptability as a mediator between social capital and career engagement - Sou, Elvo K. L.; Yuen, Mantak; Chen, Gaowei (The Career development quarterly, 2022)
The Chinese short form of Career Adapt‐Abilities Scale (CAAS‐SF) is a newly validated scale to measure career adaptability. The present study examined the psychometric properties of this measure and the role of career adaptability as a mediator between social capital and career engagement. Based on data obtained from a sample of 610 university students in Macao, it was found that the scale has good psychometric properties and is suitable for use among college students. In addition, results showed that social capital was moderately correlated with career engagement and the relationship was partially mediated by career adaptability. Implications for practice were discussed.